2020
DOI: 10.1212/wnl.0000000000010943
|View full text |Cite
|
Sign up to set email alerts
|

β-Amyloid and tau biomarkers and clinical phenotype in dementia with Lewy bodies

Abstract: ObjectiveIn a multi-center cohort of probable dementia with Lewy bodies (DLB), we tested the hypothesis that amyloid-β and tau biomarker positivity increases with age, which is modified by APOE genotype and sex, and that there are isolated and synergistic associations with the clinical phenotype.MethodsWe included 417 DLB patients (45–93 years, 31% women). Positivity on amyloid-β (A+) and tau (T+) biomarkers was determined by cerebrospinal fluid amyloid-β 1-42 and phosphorylated tau in the European cohort, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(112 citation statements)
references
References 43 publications
11
95
1
5
Order By: Relevance
“…The influence of comorbid tau on DLB clinical phenotypes, cognitive functions and brain imaging is well-documented. A key contribution to the tau-imaging has been obtained with radioligand [18F] AV-1451 based on its high affinity, selectivity and favorable kinetics [215,216]. Recent postmortem evidences have confirmed that this tracer is able to bind strongly to tau in neurofibrillary tangles and neurites without binding Aβ and, above all, it does not bind α-synuclein aggregates or Lewy bodies [214,217].…”
Section: β-Amyloid and Tau Aggregatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of comorbid tau on DLB clinical phenotypes, cognitive functions and brain imaging is well-documented. A key contribution to the tau-imaging has been obtained with radioligand [18F] AV-1451 based on its high affinity, selectivity and favorable kinetics [215,216]. Recent postmortem evidences have confirmed that this tracer is able to bind strongly to tau in neurofibrillary tangles and neurites without binding Aβ and, above all, it does not bind α-synuclein aggregates or Lewy bodies [214,217].…”
Section: β-Amyloid and Tau Aggregatesmentioning
confidence: 99%
“…They found that AD-tau related pathologic changes are common in DLB and were selectively associated with the clinical phenotype. Indeed, while amyloid-β was associated with cognitive impairment, tau pathology was associated with a lower frequency of clinical features of DLB [216]. Additionally, two multimodal PET-imaging studies should be cited [224,225].…”
Section: β-Amyloid and Tau Aggregatesmentioning
confidence: 99%
“…Evidence suggests that these Alzheimer markers likely reflect concomitant Alzheimer pathological process along with the Lewy body disease. Specifically, AD biomarkers in DLB (DLB-AD) are associated with increased age, female sex, increased APOE ε4 genotype, decreased memory, increased delusions and hallucinations, less REM-behavior sleep disorder and parkinsonism, worse language performance, faster progression, increased temporal thinning and tau pathology, and greater risk of institutionalization and mortality (2)(3)(4)(24)(25)(26)(27)(28). These findings are corroborated by post-mortem clinicopathologic studies showing that AD pathologic features (neuritic plaques and also tangles) in cases clinically defined as "probable DLB" are associated with an atypical "Alzheimerized" clinical presentation (e.g.…”
Section: Biomarkers For Alzheimer's Disease Pathologymentioning
confidence: 99%
“…Panelists agreed with the potential importance of stratifying therapeutic trial inclusions and/or outcomes based on AD biomarker profiles in LBD due to the strong association of these biomarkers with clinical outcomes, exemplified by the prospective data in the European DLB (E-DLB) consortium. Frequency of AD pathology in DLB (DLB-AD) varies between 25-89% depending on biomarker cutoffs and diagnostic criteria (2)(3)(4)(5). Distinct lines of evidence have shown that DLB-AD may represent a biological interaction of these mixed amyloid-beta, tau and alpha-synuclein pathologies.…”
Section: Ad Biomarkers In Lbdmentioning
confidence: 99%
See 1 more Smart Citation